2014
DOI: 10.1016/j.neuropsychologia.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Musicianship facilitates the processing of Western music chords—An ERP and behavioral study

Abstract: The present study addressed the effects of musicianship on neural and behavioral discrimination of Western music chords. In abstract oddball paradigms, minor chords and inverted major chords were presented in the context of major chords to musician and non-musician participants in a passive listening task (with EEG recordings) and in an active discrimination task. Both sinusoidal sounds and harmonically rich piano sounds were used. Musicians outperformed non-musicians in the discrimination task. Change-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 59 publications
5
41
0
8
Order By: Relevance
“…As MMN responses are elicited by detectable changes in the auditory stream (Näätänen et al, 2007), and P3a responses are elicited particularly by salient or unexpected deviants , Escera & Corrall, 2007, we expected at least MMN responses to be elicited by all chord contrasts. Additionally, based on previous findings (Brattico et al, 2009Koelsch et al, 1999;Putkinen et al, 2014;Tervaniemi et al, 2011;Trainor et al, 1999;Virtala et al, 2014), we expected generally facilitated chord processing as evidenced by larger and/or earlier MMN and P3a responses in musicians compared to nonmusicians.…”
Section: G Uitar Distortion Has Been Intentionallymentioning
confidence: 71%
See 3 more Smart Citations
“…As MMN responses are elicited by detectable changes in the auditory stream (Näätänen et al, 2007), and P3a responses are elicited particularly by salient or unexpected deviants , Escera & Corrall, 2007, we expected at least MMN responses to be elicited by all chord contrasts. Additionally, based on previous findings (Brattico et al, 2009Koelsch et al, 1999;Putkinen et al, 2014;Tervaniemi et al, 2011;Trainor et al, 1999;Virtala et al, 2014), we expected generally facilitated chord processing as evidenced by larger and/or earlier MMN and P3a responses in musicians compared to nonmusicians.…”
Section: G Uitar Distortion Has Been Intentionallymentioning
confidence: 71%
“…The data collected during the first part of the recording session has been reported elsewhere, including mostly the same participants (Virtala et al, 2014). During the EEG experiment, the participant watched a self-chosen DVD movie without sound and was advised not to move or blink a lot and not to pay attention to the sounds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MMN is a change-specific component of ERPs that has a peak at 150-250 ms after the onset of a deviant stimulus [7]. It has been shown that MMNs are elicited by deviant sounds in rhythmic sequences [8] and melodies [9]. Another approach is to measure an auditory steady-state response (ASSR), which can be elicited by periodically repeated sounds [10].…”
Section: Introductionmentioning
confidence: 99%